Analysis of The Implementation of Prohibition Buying of Street Vendors in Koja Sub-District North Jakarta - Guntur Adi Saputra; Eka Rofiyanti; Redjeki Agoestyowati; Dwi Agustina; Olansons Girsang (Ilomata International Journal of Social Science, 2021)
According to data on the recapitulation of orderly violations of certain places of business and businesses at the Civil Service Police Unit of North Jakarta Administrative City, there were 16,220 violations of the prohibition of trade in 2019, far from the violation of the prohibition against buying street vendors merchandises, which were only 5 violators, then this research was conducted to analyze the implementation of the prohibition of buying street vendor merchandises at Koja Subdistrict region, North Jakarta. This research method used descriptive qualitative research with data collection techniques through in-depth interviews with informants obtained by the author, in this study it was found that the DKI Jakarta Government had not widely disseminated to the public of the rules on the prohibition of buying street vendor merchandise, there was still a lack of personnel for preventing violations, and the need to revise rules related to a standard operating procedure (SOP) in prosecuting violations on the prohibition of buying street vendor merchandises